Optimization Of Video Conference With Priority Features On The Mikrotik Router - Eka Kusuma Pratama; Firmansyah Firmansyah; Tommi Alfian Armawan Sandi; Rachmawati Darma Astuti (Computer Science (CO-SCIENCE), 2022)
The emergence of new standards that must be met by all actors. Easy access to video conferencing has many positive aspects which have finally become a necessity nowadays. Each app provides easy access to increasingly sophisticated and engaging communications, making them a part of today's life. Some features that allow more than 100 participants to participate in the same video conference can have a huge impact on today's education and business world. Basic education that takes place offline only and is compiled in one place, can now be completed anytime, anywhere via a laptop or mobile phone. This is a video conference using the zoom app. Activity-intensively configured network settings are expected to maximize video conferencing when used by multiple participants. Use of mikrotik traffic priority with network packet limitations that make certain networks more prioritized first. The use of the mikrotik priority feature is expected to be able to overcome the lack of stability in video conferencing display and can be the most effective solution. Users everywhere can apply directly to their network and become an effective solution when using video conferencing applications.